Review Jurnal: Pembuatan Beras Analog dari Serelia dan Kacang-Kacangan untuk Diversifikasi Olahan Pangan - Fakhri Fargani Yusran; Heny Kusumayanti (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Rice is one of the most widely consumed staple foods in Indonesia. However, this is inversely proportional to the level of domestic rice production, so to overcome this, it is necessary to make efforts to diversify food such as analog rice. Making analog rice can use corn and beans as basic ingredients. Because corn has nutritional content, namely, water content of 10 g, protein 10,68 g, carbohydrates 74,26 g, fat 4,5 g, and fiber 2 g which is almost the same as rice and beans such as red beans have a protein content of 24,37 g, B vitamins, minerals, and fiber. The analog rice making method can use the extrusion method. In this journal review, it is hoped that we can examine the potential of rice analogues made from corn and beans for diversifying food processing.